Finding patterns of atoll morphometrics at a range of spatial scales - Johnson, Faith M.; Ortiz, Alejandra C. (Frontiers in Earth Science, 2023)
Small Island Nations, often comprised of atolls, are at considerable risk of climate change impacts from sea-level rise to coral acidification to increasing cyclone intensity; understanding how they will change in the coming century is vital for climate mitigation and resiliency. However, the morphology of atolls are not well quantified or summarized. In this work, we calculate modern atoll morphometrics on a global scale including 3,786 motu and 593 reef flats on 154 atolls. Temporal composites of Landsat imagery are created for 4 years (2015 - 2018), and are classified into motu, reef flat, open water/lagoon via unsupervised classification. Morphometrics, including widths, lengths, and area, are computed for each motu and reef flat of the atoll in python, creating a database of atolls and their associated morphometrics. Consistency in automated processing of atoll morphometrics removes spatial and user bias, enabling a better understanding of geographic patterns of atoll area and other morphometrics. Distinct differences in the distribution of motu are seen on a regional scale in French Polynesia, while globally, wider reef flats and larger motu are found closest to the equator. Globally, there is a consistent reef flat width in front of large motu (> 1 km length) of 184 ± 93 m (n = 724). Our atoll morphometric database creates a baseline of current atoll characteristics that can be expanded upon in the future and used for evaluating temporal changes to atoll islands.